2018
DOI: 10.1111/cpf.12516
|View full text |Cite
|
Sign up to set email alerts
|

Small arteries stay stiff for a longer period following vibration exercises in combination with blood flow restriction

Abstract: Results showed that small arteries stayed stiffer for a longer period of time after vibration exercises with BFR and BFR placed a greater demand on cardiovascular system. Findings also indicated that the type of exercises performed and/or the measurement location are very important and should be taken into account when examining arterial response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Of the 15 studies reporting vascular structure outcomes, 13 (87%) reported no differences between exercise with and without BFR (Table 1). Significant between group differences in vascular structure were reported in two studies following an exercise intervention of 16 weeks of BFR with resistance training (compared to high-intensity non-BFRE) (Ozaki et al, 2013) or a single session of whole-body vibration training with BFR (compared to whole-body vibration without BFR) (Karabulut, Karabulut & James, 2018).…”
Section: Vascular Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Of the 15 studies reporting vascular structure outcomes, 13 (87%) reported no differences between exercise with and without BFR (Table 1). Significant between group differences in vascular structure were reported in two studies following an exercise intervention of 16 weeks of BFR with resistance training (compared to high-intensity non-BFRE) (Ozaki et al, 2013) or a single session of whole-body vibration training with BFR (compared to whole-body vibration without BFR) (Karabulut, Karabulut & James, 2018).…”
Section: Vascular Structurementioning
confidence: 99%
“…Findings from meta-regression analyses are summarized in Table S5 ( Lopes et al (2019) excluded as case study). For vascular structure, 15 studies were included within meta-regression models reflecting four vascular structure outcomes: pulse-wave velocity (PWV) (n = 5) (Credeur, Hollis & Welsch, 2010;Clark et al, 2011;Credeur et al, 2019;Fahs et al, 2014;Figueroa & Vicil, 2011), vascular compliance (n = 5) (Karabulut, Karabulut & James, 2018;Ozaki et al, 2013;Fahs et al, 2012;Mouser et al, 2019;Sardeli et al, 2017), cardio-ankle vascular index (n = 3) (Yasuda et al, 2015a;Yasuda et al, 2015b;Yasuda et al, 2016) and arterial diameter (n = 2) (Paiva et al, 2016;Renzi, Tanaka & Sugawara, 2010). No significant associations were identified between BFRE protocol factors and effect sizes (all p-values >0.05).…”
Section: Meta-regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, studies by Kambič et al (2019 , 2021) have reported that BFR training is safe and is associated with significant improvements in muscle strength and improved muscle function in patients with coronary artery disease (CAD) and that 8weeks of BFR resistance training can significantly lower systolic and lower diastolic blood pressure with no changes in N-terminal prohormone B-type natriuretic hormone, fibrinogen, and D-dimer values in patients with CAD. Large artery compliance increased the same amount and small artery compliance less than observed with high-load exercise without restriction ( Fahs et al, 2012 ), but another study reported that small arteries stay stiff for a longer period of time following acute vibration exercises in combination with blood flow restriction ( Karabulut et al, 2018 ). With respect to the possible development of a thrombosis (as indicated by an increase in D-dimer) with BFR exercise, no reports have been found in the existing literature ( Fry et al, 2010 ).…”
Section: Safety Issues and Concernsmentioning
confidence: 99%
“…In studies involving BFR training, arterial stiffness and/or compliance are assessed non-invasively using pulse wave velocity (PWV), cardio-ankle vascular index testing (CAVI), or Doppler ultrasonography ( Hunt et al, 2013 ; Yasuda et al, 2014 ; Karabulut et al, 2018 ). PWV is defined as the velocity at which pressure wave propagates along the arterial tree ( Pereira et al, 2015 ), and lower PWV values indicate reduced arterial stiffness.…”
Section: Cardiovascular Adaptations Induced By Blood Flow Restriction Training Interventions: What Do We Know So Far?mentioning
confidence: 99%